Pulsed laser ablation synthesis of magnesiowüstite based phases with special defect clusters, interfaces and internal stress: implications for natural occurrence and engineering applications1. Issue 18 (14th May 2015) - Lin, Tsung-Yi; Lin, Shih-Siang; Chen, Shuei-Yuan; Shen, Pouyan
<x xml:space="preserve">Abstract</x> Magnesiowüstite nanocondensates with tailored shape, special interfaces, internal compressive stress and defect clusters by a pulsed laser ablation route.